Market-Based Measure as an Approach To Assessing The Performance of Football Club In Indonesia - Heri Widodo; Endra Wahyu Ningdiyah (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to analyze the financial statements of Indonesian professional football clubs using a market-based measure approach. Methodology/approach: This research method uses quantitative descriptive analysis. The data used are secondary data in the form of annual financial statements of Bali United FC football club from 2021-2024. This study used indicators such as Price to Earnings Ratio, Market to Book Value, Tobin's Q, Stock Return, and Market Capitalization. Findings: Based on the research results, all components of the Market-Based Measure Approach influence the sustainability of Bali United FC football club, namely Price to Earnings Ratio, Market to Book Value, Tobin's Q, Stock Return, and Market Capitalization. Furthermore, Bali United FC's performance, based on analysis using the Market-Based Measure approach, shows a mostly positive financial performance. This is because Bali United FC's Thobin's Q value is >1. Practical implications: The use of market-based measures can make football club performance assessments more objective because they are based on market values ​​such as brand, player value, and commercial revenue. This approach helps clubs develop more targeted business strategies, including merchandise management, digital media, and sponsorship partnerships. Clubs are also encouraged to improve governance in accordance with professional standards, thus increasing transparency and accountability. Originality/value: Using Market-Based Measures as an alternative to the traditional accounting approach (based on financial statements). The indicators used are Price to Earnings Ratio, Market to Book Value, Tobin's Q, Stock Return, and Market Capitalization.